Determination of juice removal difficulty from mash cake in cassava mash dewatering operation - Kolawole, P.; Agbetoye, L.A.S.; Ogunlowo, A.S.; Samuel, T.M. (2012)
Cassava processing equipment operators have limited knowledge; this militates against the success recorded in the research so far in cassava mash dewatering. New dewatering schemes to make food processing economical to handle are in progress. Common dewatering processes use a variety of mechanical means such as screw presses and belt presses. Experiments were conducted using three samples of TMS 4(2) 1425 variety while evaluating the difficulty of separating juice from mash cake. Average specific cake resistance (α) of 5×1011 m/kg was obtained confirming that it is moderately easy to dewatering.